Can L1 markedness and L2 input robustness account for fossilizability of L2 forms? - Nushi, Musa (Studies in Second Language Learning and Teaching, 2014)
Retraction statement The article by Musa Nushi “Can L1 markedness and L2 input robustness account for fossilizability of L2 forms?” has been recalled on account of ethical concerns.